Prospects Of Ethno And Gastronomic Tourism In The Kashkadarya Region (Texas Journal of Philology, Culture and History, 2026)
The article explores the prospects for the development of ethno- and gastronomic tourism in the Kashkadarya region. The study highlights the role of the region’s rich cultural traditions, folklore, handicrafts, and unique national cuisine in shaping its tourism potential. The paper emphasizes the importance of promoting ethno- and gastronomic tourism as a driver for economic growth, enhancing competitiveness in the international tourism market, and increasing employment opportunities for the local population